2014
DOI: 10.7202/1027807ar
|View full text |Cite
|
Sign up to set email alerts
|

Epilithon isotope composition as an environmental archive in rivers receiving wastewater

Abstract: Epilithon is a complex community of autotrophic and heterotrophic organisms that includes inert, organic and inorganic material and is attached to the surface of submersed rocks. Water samples collected in the Grand River (southwestern Ontario) in April 2011 showed that ammonium concentrations decreased downstream, whereas nitrate varied, largely dependent on weather conditions (concentrations of both chemical species were higher during winter). Epilithon δ15N-TN downstream from the Kitchener wastewater treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Indeed, consistent with our expectations and with previous research into macroalgal and epilithic δ 15 N signatures in several non-lacustrine aquatic ecosystems (Bentivoglio et al, 2016;Cejudo et al, 2014;Dailer et al, 2010;Jona-Lasinio et al, 2015;Pastor et al, 2014), we found that the magnitude and type of input reaching the lake littoral zone varied strongly in space and time. Accordingly, the δ 15 N values associated with these inputs were found to vary across sites and seasonally.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Indeed, consistent with our expectations and with previous research into macroalgal and epilithic δ 15 N signatures in several non-lacustrine aquatic ecosystems (Bentivoglio et al, 2016;Cejudo et al, 2014;Dailer et al, 2010;Jona-Lasinio et al, 2015;Pastor et al, 2014), we found that the magnitude and type of input reaching the lake littoral zone varied strongly in space and time. Accordingly, the δ 15 N values associated with these inputs were found to vary across sites and seasonally.…”
Section: Discussionsupporting
confidence: 92%
“…There is a strong need therefore for an accurate, practical and fast environmental monitoring tool. In marine, coastal, transitional water and lotic ecosystems, macroalgal and epilithic δ 15 N signatures have proved to be successful in determining the types and space-time variability of nitrogen loads (Bentivoglio et al, 2016;Cejudo et al, 2014;Cole et al, 2004;Dailer et al, 2010;Gartner et al, 2002;Jona-Lasinio et al, 2015;Orlandi et al, 2014, Pastor et al, 2013Peipoch et al, 2012;Schiller et al, 2009;Titlyanov et al, 2011;Vizzini et al, 2005), while in lacustrine ecosystems there is a lack of knowledge concerning epilithic δ 15 N signatures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epilithon biofilms are composed principally of algae, bacteria, protozoa and other smaller invertebrates (Cejudo, 2014) that are embedded in extracellular polymeric substance (EPS) including proteins, organic acids and minerals (Azim, 2005). The abundance and structure of these biofilms are dependent on the physico-chemical and environmental conditions (Sabater, 1998;Hillebrand, 2000).…”
Section: Introductionmentioning
confidence: 99%